The Relation Between IGF-1 Levels and Fasting Blood Glucose in Obese Women - Zakaria Sendy Wardana; Gadis Meinar Sari; Damayanti Tinduh (Universitas STRADA Indonesia, 2020)
This study used a cross sectional study method using 39 obese women aged 19-22 years old, Body Mass Index (BMI) 25-35 kg / m2 and Percentage Body Fat (PBF) above 30%, normal blood pressure, heart rate normal rest and normal Hemoglobin (Hb). IGF-1 levels were measured using the Enzym Link Immunosorbent Assay (ELISA) method, while the FBG measurements used ACCU-CHEK® Performance. Data analysis techniques used the Pearson Correlation test with the Statistical Package for Social Science (SPSS). The results obtained an average level of IGF-1 (11,530 ± 4,397) ng / mL and an average FBG (90,153 ± 6,659) mg / dL (r = 0.379) and (p = 0.017). Based on the results of the study, it’s concluded that there is a positive correlation of IGF-1 levels with FBG in obese women. Further research is needed to explain the physiological mechanism of the relation between IGF-1 and FBG in more detail